87.3=9(m+2.3)

Simple and best practice solution for 87.3=9(m+2.3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 87.3=9(m+2.3) equation:



87.3=9(m+2.3)
We move all terms to the left:
87.3-(9(m+2.3))=0
We calculate terms in parentheses: -(9(m+2.3)), so:
9(m+2.3)
We multiply parentheses
9m+20.7
Back to the equation:
-(9m+20.7)
We get rid of parentheses
-9m-20.7+87.3=0
We add all the numbers together, and all the variables
-9m+66.6=0
We move all terms containing m to the left, all other terms to the right
-9m=-66.6
m=-66.6/-9
m=7+1/2.5

See similar equations:

| -3(4-r)=12 | | –6=–2d+–2 | | 2x-5+11=3x | | 2/3(4/5x+3)=-1 | | 3x+6=3x+(9-3) | | 19+3.50x=5 | | 5-4y=2y+35 | | 16-8x=-24 | | -n-16=n-(5n+4) | | 3x+15-5=5x+8-2x | | 18-(7x-9)=3-4x | | -12x+5x=42 | | -6(x+12)+609=15+18 | | -(x+1)-4=-2(x+3) | | -12.8b+10.72=-13.2b+2.88 | | -3x+7=9x-28 | | 3x=48-15 | | 15xR=2000 | | 5y-3=2y+9=12y-28 | | √4x-7+5x=3(2x-1) | | -13=x+7,x= | | 2/3n-2/3=1/6n+4/3n | | 3x–8=4x | | -18=2(b+6)-10 | | 10+1/3x=360 | | -56=-3x-5x | | c=0.05•30+12.25 | | 10(1/2x+6)=10 | | -2(x+7)+142=19+11 | | -9w+1=-15-10w | | 3(2x-10)=6x | | –7(d−83)=–63 |

Equations solver categories